Circulating biomarkers in the setting of stress test-induced myocardial ischemia – a review of potential candidates for introduction into clinical practice - Zandecki, Łukasz; Zachura, Małgorzata; Barańska, Edyta; Dudzikowska, Magdalena (Medical Studies/Studia Medyczne, 2024)
The essential goal in the diagnostic approach to chronic coronary syndromes is to identify patients with significant stenoses in the coronary arteries who could benefit from invasive treatment while avoiding exposure to unnecessary interventional treatments or diagnostic procedures for patients who are unlikely to have significant stenoses in their coronary arteries. Early myocardial ischemia leads to a dynamic molecular response in the affected myocardium. A promising minimally invasive strategy is to access changes of concentrations of certain biomarkers circulating in blood during stress test-induced myocardial ischemia. This novel approach may change the landscape of non-invasive assessment of cardiac ischemia. However, there is a need for careful selection of possible candidates to be evaluated in future clinical trials. Several biomarkers have been proposed as potentially useful in this context and they are discussed in this review paper.